Bloodstain pattern classification: Accuracy, effect of contextual information and the role of analyst characteristics. Issue 2 (March 2016) - Osborne, Nikola K.P.; Taylor, Michael C.; Healey, Matthew; Zajac, Rachel
Abstract: It is becoming increasingly apparent that contextual information can exert a considerable influence on decisions about forensic evidence. Here, we explored accuracy and contextual influence in bloodstain pattern classification, and how these variables might relate to analyst characteristics. Thirty-nine bloodstain pattern analysts with varying degrees of experience each completed measures of compliance, decision-making style, and need for closure. Analysts then examined a bloodstain pattern without any additional contextual information, and allocated votes to listed pattern types according to favoured and less favoured classifications. Next, if they believed it would assist with their classification, analysts could request items of contextual information – from commonly encountered sources of information in bloodstain pattern analysis – and update their vote allocation. We calculated a shift score for each item of contextual information based on vote reallocation. Almost all forms of contextual information influenced decision-making, with medical findings leading to the highest shift scores. Although there was a small positive association between shift scores and the degree to which analysts displayed an intuitive decision-making style, shift scores did not vary meaningfully as a function of experience or the other characteristics measured. Almost all of the erroneous classifications were made by novice analysts. Highlights: Assessed analyst characteristics in relation to context effects and accuracy in BPA Experts' classifications were more reliable than novice analysts' classifications. Context effects were most apparent in relation to the provision of medical findings. Positive correlation between intuitive decision-making style and effect of context